Improving the assessment of volcanic risk from in-situ vulnerability studies: A methodological approach through the case study of the Ollagüe volcano, northern Chile - Alfredo Esquivel; Poullette Ortiz; Mauricio Rivera; Tom Gonzalez; Idir Bascuñán; María-Paz Reyes-Hardy; Yuvineza Gómez-Leyton; Amiel Nieto-Torres; Felipe Aguilera; Pablo Salazar (Progress in Disaster Science)
Volcanological studies in the Central Volcanic Zone of the Andes (CVZA) started in the 1970s and 80s. However, research on volcanic risk only increased over recent years. Specifically, in the volcanoes of northern Chile, few extant studies have focused on compiling the limited hazard and vulnerability data available from small villages located nearby. Risk assessment strategies considering vulnerability analysis have primarily focused on the physical components, whereas few works have considered vulnerability in its social, territorial, and economic dimensions. To evaluate risk dimensions around the Ollagüe volcano (Antofagasta, Chile), we integrate the analysis of elements at risk, that is, the semi-quantitative and qualitative vulnerabilities of Ollagüe, Amincha, Quebrada del Inca, and Coska villages, to volcanic hazards. The findings provide a comprehensive view of volcanic risk through the creation of several thematic volcanic risk maps, for example, extremely low social and physical risk pertains to Amincha, Coska, and Quebrada del Inca villages, whereas moderate social and low physical risk pertains to Ollagüe village. This study and the maps obtained could be extremely useful and potentially used by government institutions in charge of developing emergency and evacuation plans for disasters.